Eastward radiation of C4 crops from the Hongshan culture core region initiated around 6 ka - Licheng Guo; Qiaowen Zhang; Shiling Yang; Shangfa Xiong; Zihua Tang; Zhe Liu; Jingyi Cui; Linlin Cui (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

UPCRISPR: an ultrafast, one-tube multiplexed nucleic acid detection system for resolving the diagnostic gray zone in HPV16/18 detection - Linlin Bai; Dianwei Liu; Chunyan Qian; Weiqi Yuan; Kaiming Guo; Yao Wang; Feng Qian; Mingmin Shi; Bei Wang; Rui Wang (Analytica Chimica Acta, 2026)

Plasma-based biomimetic antigen outpost synergizes with immune checkpoint blockade to enhance antitumor immunity via dual inhibition of SOCS1 and PD-L1 pathways in dendritic cells - Siyuan Meng; Fangnan Lv; Jieqing Chen; Linlin Tao; Hao Guo; Danhui Wang; Jie Sun; Jian Li; Ning Liu; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2026)

Organophosphate flame retardants and incident type 2 diabetes: Integrating population evidence, mechanistic insights, and effect modification by healthy lifestyle - Xueyan Wu; Yilin Zhou; Yue Nie; Haoran Xu; Hengrui Liu; Mengke Cheng; Yao Guo; Fangyuan Lin; Xin Tang; Peihan Chen; Dandan Wei; Jian Hou; et al. (Journal of Hazardous Materials, 2026)

Aurantio-Obtusin Attenuates Aβ-Induced Cognitive Impairment and Synaptic Dysfunction by Suppressing Neuroinflammation in Mice - Xueying Feng; Wei Yu; Song Guo; Yanyan Ji; Junhua Li; Ling Wang; Guolu Zhong; Shiyi Li; Linlin Niu; Danxin Zhu; Kan Zhou; Yehong Du (Journal of Neuroimmune Pharmacology, 2026)

Effect of coupled temperature-humidity drying on multi-scale structure and in vitro digestibility of corn resistant starch - Qing Su; Lirong Chen; Linlin Sun; Xingya Wang; Yuqiu Guo; Meimei Zhao; Kaichang Liu; Kuijie Gong (Food Chemistry, 2026)

High internal phase emulsions stabilised by amyloid fibrils from 7S/11S soybean protein at varying ratios: Study on interfacial behaviour, rheological properties and curcumin delivery potential - Tianlu Han; Ruqi Guo; Yuexin An; Yuyang Huang; Linlin Liu; Zihan Wang; Ying Zhu; Xiuqing Zhu (Food Chemistry, 2026)

Food-derived inositol derivatives mitigate high-fat diet-induced adiposity by attenuating inflammation and promoting adipocyte browning in mice - Xiaochen Guo; Mengjie Xu; Linlin Liu; Qinghui Lin; Rui Gao; Ruoxuan Xu; Wei Yu; Zhongmei Liang; Pengfei Wu; Zehan Dong; Zhen Xie; Nan Meng; et al. (Food Bioscience, 2026)

Responses of sedimentary magnetic susceptibility and metal contents to climate and anthropogenic activity changes: examination on lake records across the Asian monsoon region - Haiyang Yu; Shuangchi Liu; Jule Xiao; Xu Wang; Linlin Cui; Licheng Guo; Xueting Wang; Shihao Zhang (CATENA, 2026)

Compositing high-resolution SDGSAT-1 nighttime light data by ranking of structural image features - Martino Pesaresi; Johannes H. Uhl; Linlin Lu; Panagiotis Politis; Dong Liang; Michele Melchiorri; Inés Marí Rivero; Katarzyna Krasnodębska; Huadong Guo (Remote Sensing of Environment, 2026)

Unlocking iron-chromium flow batteries: Conquering kinetics and crossover for affordable grid storage - Jiaxin Meng; Guozhen Zhang; Weizhai Bao; He Liu; Cong Guo; Jingfa Li; Feng Yu; Linlin Yang; Aishui Yu (Chemical Engineering Journal, 2026)

Advances in bacterial synthesis pathways of bioflocculants and their applications in mine wastewater treatment - Linlin Zhang; Zhaofeng Liu; Qiang Guo; Jiawei Tang; Xiaoduan Li; Qun Wang (World Journal of Microbiology and Biotechnology, 2026)

Seven neonicotinoids and twenty-two metabolites in seven food matrices by optimized QuEChERS-HPLC-MS/MS and dietary risk assessment - Zhenzhen Zhou; Xueyan Zhao; Junfeng Lu; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie; Fajun Tian (Food Chemistry, 2026)

Multifunctional nanoemulsion co-delivering Lactobacillus plantarum supernatant and Litsea cubeba essential oil: Construction and application in fiddlehead fern preservation - Jiayue Song; Dengyi Ye; Wenjia Li; Qiao Guo; Yanan Zhang; Xiyu Wang; Ping Tang; Ping Chen; Linlin Xu (Food Bioscience, 2026)

Ultrastructural Evidence of Altered Dendritic Morphology in the Prefrontal Cortex of Alzheimer's Model Rats - Jinyue Guo; Jing Liu; Yanchao Zhang; Jiazheng Liu; Hao Zhai; Linlin Li; Hua Han (Neuroscience Bulletin, 2026)

Integrating SDGSAT-1 glimmer imagery with Sentinel-1/2 data for high-resolution building height estimation - Zilu Li; Huadong Guo; Linlin Lu; Yifang Ban; Qi Zhu; Dong Liang (Remote Sensing of Environment, 2026)

Coastal land reclamation induced estuarine nutrient-related eutrophication stressors: phenomena, evaluation and management strategies - Linlin Wang; Yuehua Guo; Wenbin Liu; Huaihao Shao; Shuangliang Dai; Lin Mu; Xianzhong Mao; Hongsheng Bi; Kai Zhou; Xiaoyu Lei (Journal of Hydrology, 2026)

Leveraging butter-whey protein interactions to engineer starch-based inks for high-fidelity 3D food printing - Xinyu Wei; Limin Cheng; Wenchao Liu; Zhenbin Liu; Chaofan Guo; Linlin Li; Weiwei Cao; Xu Duan; Guangyue Ren; Weihua Guo; Wei Chen; Lifeng Pan (Journal of Food Engineering, 2026)

Amyloid fibrillation of different ratios of 7S/11S soy protein: comparison of fibril structural characteristics and analysis of the potential for preparing high-internal-phase emulsions - Tianlu Han; Lidan Qiu; Qinlin Hu; Ruqi Guo; Ying Zhu; Yuyang Huang; LinLin Liu; Ying Wang; Xiuqing Zhu (Food Hydrocolloids, 2026)

Holocene wildfire activity archived in East Asian marginal sea: Linkages to climate variability and human civilization - Linlin Chen; Yazhi Bai; Zhigang Guo; Weini Chong; Yuying Zhang; Jinming Bai; Yaru Liu; Haiyan Fang; Limin Hu (CATENA, 2026)

Machine learning based prediction of mechanical properties in carbon fiber recovered through pyrolysis - Xiang Guo; Tian Li; Chunting Liu; Meng Zhang; Hao Li; Jinrui Li; Yihua Zhang; Chunmei Zeng; Shuwu Wei; Linlin Pei; Fang Liu; Da Chen (Waste Management, 2026)

Cadmium exposure is associated with impaired ovarian function: Potential role of cadmium-induced ferroptosis in granulosa cells - Jing Li; Yutong Wang; Yali Huang; Nidong Li; Yingxin Zhu; Shengli Lin; Linlin Wang; Wei Guo; Lailai Yan; Chan Tian; Ying Wang (Journal of Hazardous Materials, 2026)

Globally synchronous acceleration of soil formation approximately 12,000 years ago - Licheng Guo; Qiaowen Zhang; Haozhong Xue; Shangfa Xiong; Shiling Yang; Zihua Tang; Linlin Cui; Jingyi Cui; Yongda Wang; Shihao Zhang (Global and Planetary Change, 2026)

Unveiling structural evolution during high-moisture extrusion of soy protein isolate-wheat gluten systems with soy dietary fiber: A sudden shutdown-based study - Ruqi Guo; Haojia Zhang; Yang Gao; Zihan Wang; Yinlin Wang; Ying Zhu; Linlin Liu; Xiuqing Zhu (Food Chemistry, 2026)

A novel bacteriophage pAEh1 for controlling Aeromonas hydrophila infection in aquaculture - Sifan Jiang; Boyang Zhou; Tongping Zhang; Rongsi Dai; Su Long; Linlin Yang; Mingwang He; YanJiao Fu; Jiajing Guo; Zhipeng Gao (Fish & Shellfish Immunology, 2026)

Black phosphorus quantum dots regulate inflammation and neural stem cells differentiation via Notch1 signaling through cell adhesion - Lu Chen; Yongyuan Guo; Lusen Shi; Shiji Zhang; Linlin Jiang; Yong Chang; Haoran Liu; Zihang Wang; Na Li; Shiqing Feng (Chemical Engineering Journal, 2026)

Interactive effect of children’s copper exposure and socioeconomic status on preschoolers’ cognitive development - Hualong Zhen; Linlin Zhu; Xuemei Hao; Jingru Lu; Yufan Guo; Chunmei Liang; Juan Tong; Fangbiao Tao; Jiong Li; Kun Huang (NeuroToxicology, 2026)

Synergistic DFT and experimental design of Ga/W Co-Doped SnS2 microspheres with enriched sulfur vacancies for enhanced NO2 sensing - Wei Zhao; Lanlan Guo; Xin Shi; Linlin Dong; Yingli Yang; Xueli Yang; Xiaolian Liu; Guodong Wang; Yan Wang (Chemical Engineering Journal, 2026)

Deciphering Ferroptosis-Related Astrocyte Subpopulations and Diagnostic Biomarkers in Parkinson’s Disease through RNA Transcriptomics - Zhongying Gong; Dan Guo; Yufeng Lin; Zhiwei Liu; Mengdi Lv; Xinxin Liu; Mingshuo Sun; Linlin Wang; Tianman Zhao; Zhiyun Wang; Xue Xue (Molecular Neurobiology, 2026)

Effect of cAMP concentration on apoptosis of sheep granulosa cells in vitro - Wenhao Wang; Linlin Pei; Peilin Guo; Andi Qiao; Shuyan Guo; Xin Xu; Chunjie Liu (In Vitro Cellular & Developmental Biology - Animal, 2026)

prepIMS: a robust data preprocessing workflow for ion mobility mass spectrometry imaging - Linlin Wang; Chengyi Xie; Lei Guo; Thomas Ka Yam Lam; Chris Kong Chu Wong; Mudassir Shah; Xiangnan Xu; Jianing Wang; Jingjing Xu; Jiyang Dong; Zongwei Cai (Analytica Chimica Acta, 2026)

Learning to reason over multi-granularity knowledge graph for zero-shot urban land-use mapping - Yansheng Li; Yu Wang; Lei Yu; Bo Dang; Gang Xu; Zhenyu Zhong; Yuning Wu; Xin Guo; Kang Wu; Zheng Li; Linlin Wang; Jian Wang; et al. (Remote Sensing of Environment, 2025)

The influence of different emulsifiers on dotted gizzard Shad (Konosirus punctatus) oil emulsions - Ying Guo; Linlin Wang; Kaiyi Wang; Li Li; Mengting Wei; Xin Wang; Zhen Wang; Baojie Jiang; Juanjuan Shao; Jilu Sun (Food Chemistry, 2025)

Investigating the aroma transition during rapid mango ripening driven by dynamic catabolism of fatty acids - Yuanping Wang; Zhenjiang Zhou; Yonghao Liu; Rongli Pang; Xi Zhao; Qi Chen; Linlin Guo; Baiyi Lu (Food Chemistry, 2025)

Biochar-induced strong microbial carbon limitation prompts organic carbon sequestration and plant growth in antibiotic-contaminated soil - Linlin Qiu; Tim J. Daniell; Muhammad Nafees; Yihao Chen; Shuyu Zhou; Weihong Wu; Jia Du; Qingwei Zhou; Meiqing Jin; Weiying Ji; Jiaying Ge; Hongyan Guo (Plant and Soil, 2025)

Comparative analysis of storage temperatures and forchlorfenuron treatment concentrations on physiological quality and primary metabolites in kiwifruit during storage - Xiaofan Qi; Chengkui Qiao; Lijun Han; Ming Zhuang; Mengyuan Cao; Caixia Wang; Linlin Guo (Postharvest Biology and Technology, 2025)

Tetraether-based temperature record from Lake Xingyun in southwestern China since late MIS3 and implication for regional differences in temperature reconstruction - Haiyang Yu; Xu Wang; Ming Ji; Shihao Zhang; Gaochao Pan; Licheng Guo; Linlin Cui; Xueyun Ma; Wubiao Li; Dongsheng Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Efficient degradation of tetracycline using boron assistant Co3O4 activated PAA: Formation of B-O-Co and accelerated electron transfer - Peng Lu; Jialin Jiang; Linlin Miao; Yun Guo; Haizhu Chen; Shuai Zhou; Jiutao An (Journal of Environmental Chemical Engineering, 2025)

Double synergistic strategy: mechanism of acetone sensing performance enhancement by Pt@Cu3(HHTP)2 derivatives modifying three-dimensional inverse opal In2O3 - Lanlan Guo; Jiaru Yang; Yuying Cai; Linlin Dong; Yingli Yang; Xueli Yang; Xiaolian Liu; Guodong Wang; Yan Wang (Chemical Engineering Journal, 2025)

Engineering efficient and stable CsPbBr3 perovskite nanocrystals via multi-functional molecular mediated surface strategy toward white light-emitting devices - Hanyun Yang; Haoqi Zhu; Linlin Ma; Mengwei Luo; Hang Guo; Lepeng Zhou; Wenxu Sun; Bin Xue; Lei Zhang (Chemical Engineering Journal, 2025)

SIMPLE: A One-Pot RPA-Cas12b Method for Single Nucleotide Variations Identification with an Expanded Scope and Clinical Applications - Kaiming Guo; Yongkang Lai; Yiru Han; Linlin Bai; Ting Wang; Shengzhou Wang; Ziqin Zhang; Dianwei Liu; Yanju Chen; Jiulong Zhao; Yanan Pang; Feng Qian; et al. (Phenomics, 2025)

SagMSI: A graph convolutional network framework for precise spatial segmentation in mass spectrometry imaging - Mudassir Shah; Linlin Wang; Lei Guo; Chengyi Xie; Thomas Ka-Yam Lam; Lingli Deng; Xiangnan Xu; Jingjing Xu; Jiyang Dong; Zongwei Cai (Analytica Chimica Acta, 2025)

Global variations of urban form: Characterization and quantification through intelligent remote sensing image analysis - Jie Chen; Geng Sun; Yongze Song; Yinxia Cao; Cheolhee Yoo; Ya Guo; Chunhong Zhao; Linlin Lu; Qihao Weng (Sustainable Cities and Society, 2025)

Mechanisms for sulfadiazine effective mitigation in biochar-amended soil: From antibiotic resistance to soil microbial community composition and function - Linlin Qiu; Luxi Niu; Muhammad Nafees; Shuyu Zhou; Weihong Wu; Jia Du; Qingwei Zhou; Meiqing Jin; Hongyan Guo (Journal of Environmental Management, 2025)

Differences in the distribution of exogenous nucleotide intake in the colon of neonatal rats and its impact on early-life metabolism, gut, gut microbiota, and skeletal development - Zhihao Qu; LiLi Zhu; Min Guo; Kexin Shang; Peijun Tian; Linlin Wang; Gang Wang; Heng Zhang; Wei Chen (Food Bioscience, 2025)

Performance and mechanism of tris(2-chloropropyl) phosphate (TCPP) removal in an iron-carbon microelectrolysis constructed wetland system - Yongqiang Wang; Linlin Li; Xiaochun Guo; Aiwen Wang; Yunhao Pan; Jun Ma; Shaoyong Lu; Dongmei Liu (Chemical Engineering Journal, 2025)

MVPCR: Multiplex Visual Detection Strategy Based on Ultrafast PCR for Point-of-Care Pathogens Detection Within 10 Min - Ziqin Zhang; Cui Wu; Linlin Bai; Kaiming Guo; Ting Wang; Dianwei Liu; Mingrui Zhu; Feng Qian; Fang Zhang; Rui Wang (Phenomics, 2025)

Cover Image - Linlin Yang; Weiming Zhong; Tao Tang; Mingwang He; Tongping Zhang; Boyang Zhou; Yulong Yin; Jiajing Guo; Zhipeng Gao (Reviews in Aquaculture, 2025)
The cover image is based on the article Phage‐Based Biocontrol Strategies and Application in Aquatic Animal Disease Prevention and Control by Zhipeng Gao et al., https://doi.org/10.1111/raq.70024 . image

Phage‐Based Biocontrol Strategies and Application in Aquatic Animal Disease Prevention and Control - Linlin Yang; Weiming Zhong; Tao Tang; Mingwang He; Tongping Zhang; Boyang Zhou; Yulong Yin; Jiajing Guo; Zhipeng Gao (Reviews in Aquaculture, 2025)
Aquaculture is essential for meeting future demands for food, yet it faces significant losses from infectious bacterial diseases. Aquaculture has recently been critically imperiled by the emergence of multi‐drug‐resistant bacteria, as it relies significantly on the use of antibiotics for prevention and treatment. The emergence of multidrug‐resistant bacteria poses a critical threat to aquaculture, which heavily relies on antibiotics for prevention and treatment. Bacteriophage (phage) therapy has regained attention with the spread of drug‐resistant bacteria. Phages are viruses that specifically infect bacteria and archaea. As a promising therapeutic strategy for aquatic bacterial diseases, phage therapy offers strong specificity, low resistance potential, rapid metabolism, ease of development, and cost‐effectiveness. In this review, we discuss the advantages, opportunities, and challenges of phage therapy, summarizing the status of research and highlighting emerging technologies aimed at enhancing phage therapy in aquaculture. Finally, the review looks to the future, identifying scientific and technological advances necessary to establish phage therapy as a viable and universal alternative to antibiotics in aquaculture.

Protective effects of resveratrol on honeybee health: Mitigating pesticide-induced oxidative stress and enhancing detoxification - Linlin Liu; Min Shi; Yanyan Wu; Jiali Hao; Junxiu Guo; Shanshan Li; Pingli Dai; Jing Gao (Pesticide Biochemistry and Physiology, 2025)

From field to table: Reducing residual toxicity and risk of four pesticides via washing and blanching of cowpea (Vigna unguiculata (L.) Walp.) - Shuangwei Zhang; Yajing Guo; Shanshan Zhu; Linlin Guo; Xinglu Pan; Jun Xu; Fengshou Dong; Yongquan Zheng; Xiaohu Wu (Food Chemistry, 2025)

Polystyrene microplastics (PS-MPs) harness copper presence and promote impairments in early zebrafish (Danio rerio) larvae: Developmental, biochemical, transcriptomic approaches and nontargeted metabolomics approaches - Liqiao Zhang; Dongqiu Guo; Xinrui Dong; Longxiao Liu; Mengqi Jiang; Linlin Song; Xia Wang (Environmental Research, 2025)

Physiological and transcriptomic responses of the microalga Isochrysis galbana during exposure to Hg(II) stress - Linlin Zhang; Na Li; Xinfeng Xiao; Linke Guo; Wenfang Li; Yanjun Li; Fei Ling (World Journal of Microbiology and Biotechnology, 2025)

Diffusion coefficients of water in CO2 under the condition of CO2 sequestration in saline aquifers - Zhe Wang; Linlin Lin; Huirong Guo; Wanjun Lu (Journal of Hydrology, 2025)

Convert iron tailings waste into a novel Mg-Fe-Al hybrid magnetic coagulant for enhanced pretreatment of swine wastewater - Linlin Hao; Jingshuang Yan; Jiaoying Guo; Nannan Wang; Ming Zeng (Journal of Environmental Chemical Engineering, 2025)

Association of Urinary Phthalate Metabolites with Lipid Profiles and the Mediating Role of Serum Globulin: A Repeated-Measures Study - Kun Huang; Linlin Liu; Lei Zhao; Miao Liu; Chongjian Wang; Wenting Guo; Huihua Yang; Rui Zhu; Xiaomin Zhang (Exposure and Health, 2025)

Antifungal activity and active compound identification of Myrothecium spp. against grape anthracnose and gray mold - Linlin Gao; Yijie Zhai; Jiajia Wu; Yuwei Li; Yanchun Fan; Junqiang Guo; Xiping Wang; Zhi Li (Pesticide Biochemistry and Physiology, 2025)

Volatile profile of postharvest hardy kiwifruits treated with chitosan-silica nanocomposite coatings - Mengyuan Cao; Chengkui Qiao; Lijun Han; Ming Zhuang; Shiyu Wang; Rongli Pang; Linlin Guo; Mingqin Yang; Momo Gui (Food Research International, 2025)

Residual behaviors and health risk assessment of dinotefuran, flonicamid, and their metabolites during apple growth, storage, and processing - Fajun Tian; Zhenzhen Zhou; Junfeng Lu; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie (Food Research International, 2025)

Effect of freezing-thawing treatment on the quality and structure of soymilk gels induced by different coagulants - Ying Zhu; Wenhua Lei; Lidan Qiu; Simiao Liu; Ruqi Guo; Yuyang Huang; Linlin Liu; Mingshou Lv; Bingyu Sun; Min Qu; Ying Sun; Xiuqing Zhu (Food Hydrocolloids, 2025)

Butyrylated modification of corn starch alleviates autism-like behaviors by modulating 5-hydroxytryptamine metabolism and gut-brain neural activity - Wentian Li; Qingmin Kong; Min Guo; Linlin Wang; Peijun Tian; Jingyu Lu; Jianxin Zhao; Wei Chen; Gang Wang (Carbohydrate Polymers, 2025)

The role of telomere shortening in ambient ozone exposure-related insulin resistance - Ruiying Li; Gongbo Chen; Wei Liao; Yinghao Yuchi; Xiaohuan Yang; Ziyuan Zhang; Xiaotian Liu; Zhenxing Mao; Linlin Li; Jiahui Zhao; Huijun Li; Wenqian Huo; et al. (Journal of Hazardous Materials, 2025)

Provincial localization framework for SDGs in China: Enhancing support for sustainable governance - Wen Song; Shisong Cao; Mingyi Du; Linlin Lu; Huadong Guo; Sirui Wang; Yue Liu; Xiaoxuan Li (Applied Geography, 2025)

Contribution of mitochondria to postmortem muscle tenderization: a review - Feng Huang; Zhenjiang Ding; Jinsong Chen; Bing Guo; Linlin Wang; Chunmei Liu; Chunhui Zhang (Critical Reviews in Food Science and Nutrition, 2025)

A comprehensive review on iron‒carbon microelectrolysis constructed wetlands: Efficiency, mechanism and prospects - Yongqiang Wang; Linlin Li; Xiaochun Guo; Aiwen Wang; Yunhao Pan; Jun Ma; Shaoyong Lu; Dongmei Liu (Water Research, 2025)

Dietary nucleotides drive changes in infant fecal microbiota in vitro and gut microbiota-gut-brain development in neonatal rats: A potential “nitrogen source” for early microbiota growth - Zhihao Qu; Bo Zhang; Guopeng Lin; Min Guo; Peijun Tian; Linlin Wang; Wei Chen; Heng Zhang; Gang Wang (Food Chemistry, 2025)

Bimetallic RuCo anchored CoFe2O4 nanosheets to realize in-depth electronic modulation for boosted structural reconstruction and efficient seawater electrolysis - Xueling Wei; Youjun Huang; Qiguan Wang; Linlin Dang; Kai Zhang; Qing Guo; Wenhu Li; Taotao Ai; Sumin Wang (Chemical Engineering Journal, 2025)

Distribution of microplastics in the soils of a petrochemical industrial region in China: Ecological and Human Health Risks - Yuting Guo; Rongshan Wu; Heng Zhang; Changsheng Guo; Linlin Wu; Jian Xu (Environmental Geochemistry and Health, 2025)

N18 ring: A building block for constructing 1D and 2D polymeric nitrogen frameworks - Yuxiang Gao; Ying Zhang; Shuang Liu; Bo Jin; Linlin Guo; Xu Guo; Zhen Yao; Peng Wang; Bingbing Liu (Science Bulletin, 2024)

The mediating role of abnormal ZEB1 methylation in the association between nickel exposure and non-syndromic orofacial cleft - Yongyan Chen; Yaquan Pan; Lijun Liu; Yingnan Guo; Lei Jin; Aiguo Ren; Linlin Wang (Reproductive Toxicology, 2024)

Elementomics of 32 elements in cord serum depicts the risk of orofacial clefts: A case-control study in Shanxi, China - Jing Wei; Dezheng Fu; Siyu Guo; Tian Tian; Yun Huang; Zhiwen Li; Linlin Wang; Lei Jin; Weiping Ye; Aiguo Ren; Shengju Yin (Environmental Pollution, 2024)

Prospective study on the joint effect of persistent organic pollutants and glucose metabolism on chronic kidney disease: Modifying effects of lifestyle interventions - Dandan Wei; Jiayu Shi; Haoran Xu; Yao Guo; Xueyan Wu; Zhiwei Chen; Taimeng Chen; Huilin Lou; Erbao Han; Guozhen Han; Yumeng Yan; Xiaotian Liu; et al. (Science of The Total Environment, 2024)

Integrated proteome and pangenome analysis revealed the variation of microalga Isochrysis galbana and associated bacterial community to 2,6-Di-tert-butyl-p-cresol (BHT) stress - Linke Guo; Shuangwei Li; Dongle Cheng; Xiao Lu; Xinying Gao; Linlin Zhang; Jianjiang Lu (World Journal of Microbiology and Biotechnology, 2024)

Insights into the uptake, accumulation, and metabolism of UV-328 in lettuce (Lactuca sativa L.) and radish (Raphanus sativus L.) - Bingru Li; Zhenzhen Yao; Qi Liu; Linlin Guo; Zhihong Ma; Cheng Li (Chemosphere, 2024)

Ultrasensitive monitoring of PCB77 in environmental samples using a visible-driven photoelectrochemical sensing platform coupling with exonuclease I assisted in target recycling - Lining Su; Guizhen Wang; Linlin Zhao; Yuan Deng; Yujing Guo; Yong Xiao; Huanwen Wang; Chuan Dong; Lifang Fan (Science of The Total Environment, 2024)

Effects of storage and processing on the residual distribution and behavior of five preservatives and their metabolites in pomegranate - Fajun Tian; Junfeng Lu; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie (Food Chemistry, 2024)

Changes of 22 pesticide residues and 3 metabolites during the common processing of Auricularia auricula-judae - Mingqin Yang; Fayi Qin; Lijun Han; Chengkui Qiao; Ming Zhuang; Mengyuan Cao; Shiyu Wang; Rongli Pang; Linlin Guo (Food Control, 2024)

The impact of block morphology on urban microclimates: A case study of three cities in cold regions of China - Linlin Guo; Xiaohua Guo; Baofeng Li; Endong Wang (Urban Climate, 2024)

Daily trunk radial growth patterns in relation to precipitation in orange trees in the dry-hot valley region of Southwest China - Xuehui Wei; Dianyu Chen; Panpan Hou; Xiaotao Hu; Lucheng Qiu; Jingying Zhang; Xingwu Duan; Linlin Zhang; Jing Guo (Journal of Hydrology, 2024)

A multi-omics-based investigation into the regulation of phenolics in fresh maize kernels at different developmental stages - Xiaomin Tian; Di Han; Linlin Sun; Yuqiu Guo; Kaichang Liu; Lirong Chen; Kuijie Gong (Journal of Cereal Science, 2024)

Immobilization of pancreatin based on ultrasound-assisted polydopamine functionalized magnetic porous chitosan for the detoxification of ochratoxin A in wine - Saiqun Wang; Tianmin Guo; Xiaoxue Mei; Xinyi Zhong; Linlin Gao; Rui Cai; Tianli Yue; Yahong Yuan; Zhenpeng Gao; Zhouli Wang (Food Chemistry, 2024)

Constructing efficient lithium salt dissociation solid-state electrolytes with high conductivity and transference number of Li ions for stable all-solid-state lithium batteries - Zengcai Guo; Shimin Liao; Feng Li; Linlin Shi; Bihai Su; Jingbo Mu; Yanming Wang; Zhongkai Huang; Feng Xu; Chaowen Guan (Chemical Engineering Journal, 2024)

N-Doped Carbon Dots for Selective Detection of Fe3+ and Degradation of Fe3+/Basic Red 9 Complexes in Water Samples - Caixia Wang; Chengkui Qiao; Fajun Tian; Linlin Guo; Ruiping Wang; Jun Li; Tao Pang; Rongli Pang; Hanzhong Xie (Journal of Fluorescence, 2024)

Unlocking enhanced photocatalytic power: Donor-acceptor synergy in non-metallic g-C3N4 hollow nanospheres - Xinhua He; Xiandi Guo; Zijie Xia; Linlin Wang; Zheng Jiao (Chemosphere, 2024)

Recent Holocene activity and regional tectonic significance of the northern segment of the red river fault zone - Long Guo; Zhongtai He; Zhikun Ren; Linlin Li; Xingao Li; Haomin Ji; Kuan Liang; Xin Tan (Journal of Structural Geology, 2024)

Elevated lead mobility in sediments of a eutrophic drinking water reservoir during spring and summer seasons: Insights from isotopic signatures - Zhenghua Tao; Guogan Peng; Fengyuan Chen; Qingjun Guo; Rongfei Wei; Ke Pan; Yinan Deng; Linlin Jiao; Zhen Zhang; Shanshan Chen; Tianxiang Xia (Journal of Hazardous Materials, 2024)

Ecological restoration for eutrophication mitigation in urban interconnected water bodies: Evaluation, variability and strategy - Linlin Wang; Huaihao Shao; Yuehua Guo; Hongsheng Bi; Xiaoyu Lei; Shuangliang Dai; Xianzhong Mao; Kai Xiao; Xiaomei Liao; Hao Xue (Journal of Environmental Management, 2024)

Spatial distribution and regional tectonic significance of the newly discovered Kalawenguquan fault in the interior of the Tian Shan Mountain Range, Western China - Xingao Li; Zhongtai He; Zhikun Ren; Linlin Li; Lei Wang; Haomin Ji; Xiaoxiao Zhu; Long Guo; Liangliang Wu (Journal of Asian Earth Sciences, 2024)

Dissipation behavior and risk assessment of imidacloprid and its metabolites in apple from field to products - Fajun Tian; Junfeng Lu; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie (Chemosphere, 2024)

Low energy-consumption oriented membrane fouling control strategy in anaerobic fluidized membrane bioreactor - Lu Liu; Ze Guo; Yihe Wang; Linlin Yin; Wei Zuo; Yu Tian; Jun Zhang (Chemosphere, 2024)

An engineered DNA aptamer-based PROTAC for precise therapy of p53-R175H hotspot mutant-driven cancer - Lingping Kong; Fanlu Meng; Ping Zhou; Ruixin Ge; Xiaoshan Geng; Zhihao Yang; Guo Li; Linlin Zhang; Jing Wang; Jinfeng Ma; Cheng Dong; Jun Zhou; et al. (Science Bulletin, 2024)

Chromium levels in placental tissue and neural tube defects: Association and mechanistic study - Yongyan Chen; Yingnan Guo; Chengrong Wang; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Environmental Pollution, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

PCDH11X mutation as a potential biomarker for immune checkpoint therapies in lung adenocarcinoma - Manjiao Liu; Meijia Yang; Bei Zhang; Sijian Xia; Jie Zhao; Linlin Yan; Yong Ren; Hao Guo; Jie Zhao (Journal of Molecular Medicine, 2024)

Mechanistic approach of tannery wastewater and sulfadiazine mutual toxicity in wheat (Triticum aestivum L.) and mitigation through exogenous application of gallic acid. - Muhammad Nafees; Muhammad Azhar Ali; Linlin Qiu; Ying Yin; Meiling Xu; Guobing Wang; Shafaqat Ali; Hongyan Guo (Chemosphere, 2024)

Effect-directed analysis of androgenic compounds from sewage sludges in China - Tongtong Xiang; Chunzhen Shi; Yunhe Guo; Jie Zhang; Weicui Min; Jiazheng Sun; Jifu Liu; Xiliang Yan; Yanna Liu; Linlin Yao; Yuxiang Mao; Xiaoxi Yang; et al. (Water Research, 2024)

A robust transformer-based pipeline of 3D cell alignment, denoise and instance segmentation on electron microscopy sequence images - Jiazheng Liu; Yafeng Zheng; Limei Lin; Jingyue Guo; Yanan Lv; Jingbin Yuan; Hao Zhai; Xi Chen; Lijun Shen; LinLin Li; Shunong Bai; Hua Han (Journal of Plant Physiology, 2024)

Influence of point bars on nitrogen transport and reaction in riparian zones - Xunchuan Song; Ying Liu; Defu Liu; Jinghong Feng; Linlin Li; Yongsheng Guo; Junxiong Luo; Weiping Jiang (Journal of Hydrology, 2024)

Influence of mixing uniformity between stabilisation materials and contaminated soil on the stabilisation efficiency of heavy metals - Yunlong Zhang; Lixia Sun; Bo Wu; Meng Zhang; Shuhai Guo; Linlin Li; Shuqi Li; Longlong Qu (Journal of Environmental Chemical Engineering, 2024)

Recent progress in the antidegradation strategies of two-dimensional transition metal carbides (MXenes) - Ying Li; Yudi Li; Linlin Zhao; Siyu Chen; Siren Guo; Xulin Yang; Pan Wang; Kui Li; Fan Lei; Wei Feng; Zihao Mou; Hanjun Wei (Journal of Environmental Chemical Engineering, 2024)

Polycyclic aromatic hydrocarbons exposure and arterial stiffness-related plasma miRNAs: A panel study - Ziqian Zhang; Conghua Bai; Lei Zhao; Linlin Liu; Wenting Guo; Miao Liu; Huihua Yang; Xuefeng Lai; Xiaomin Zhang; Liangle Yang (Environmental Toxicology and Pharmacology, 2024)

Seismic risk assessment of self-centering prestressed concrete frames with sliding and masonry infill walls: experimental and numerical models - Ruizhao Zhu; Tong Guo; LinLin Xie; Lianglong Song; Kun Yang; Solomon Tesfamariam (Bulletin of Earthquake Engineering, 2024)

A transferable approach to assessing green infrastructure types (GITs) and their effects on surface urban heat islands with multi-source geospatial data - Linlin Lu; Huadong Guo; Qihao Weng; Carlos Bartesaghi-Koc; Paul Osmond; Qingting Li (Remote Sensing of Environment, 2024)

A comprehensive “quality-quantity-activity” approach based on portable near-infrared spectrometer and membership function analysis to systematically evaluate spice quality: Cinnamomum cassia as an example - Ziwei Zou; Bingjian Guo; Yue Guo; Xiaolong Ma; Sanshan Luo; Linlin Feng; Ziping Pan; Lijun Deng; Shihan Pan; Jinbin Wei; Zhiheng Su (Food Chemistry, 2024)

Variant effect predictors: a systematic review and practical guide - Cristian Riccio; Max L. Jansen; Linlin Guo; Andreas Ziegler (Human Genetics, 2024)
Large-scale association analyses using whole-genome sequence data have become feasible, but understanding the functional impacts of these associations remains challenging. Although many tools are available to predict the functional impacts of genetic variants, it is unclear which tool should be used in practice. This work provides a practical guide to assist in selecting appropriate tools for variant annotation. We conducted a MEDLINE search up to November 10, 2023, and included tools that are applicable to a broad range of phenotypes, can be used locally, and have been recently updated. Tools were categorized based on the types of variants they accept and the functional impacts they predict. Sequence Ontology terms were used for standardization. We identified 118 databases and software packages, encompassing 36 variant types and 161 functional impacts. Combining only three tools, namely SnpEff, FAVOR, and SparkINFERNO, allows predicting 99 (61%) distinct functional impacts. Thirty-seven tools predict 89 functional impacts that are not supported by any other tool, while 75 tools predict pathogenicity and can be used within the ACMG/AMP guidelines in a clinical context. We launched a website allowing researchers to select tools based on desired variants and impacts. In summary, more than 100 tools are already available to predict approximately 160 functional impacts. About 60% of the functional impacts can be predicted by the combination of three tools. Unexpectedly, recent tools do not predict more impacts than older ones. Future research should allow predicting the functionality of so far unsupported variant types, such as gene fusions. URL: https://cardio-care.shinyapps.io/VEP_Finder/ . Registration: OSF Registries on November 10, 2023, https://osf.io/s2gct .

Uptake, accumulation and metabolism of UV-320 in vegetables and its impact on growth and quality - Bingru Li; Zhenzhen Yao; Dizhe Wei; Linlin Guo; Zhihong Ma; Cheng Li (Science of The Total Environment, 2024)

CO2 methanation reaction over La-modified NiAl catalysts derived from hydrotalcite-like precursors - Linlin Zhou; Xiaoming Guo; Xu Hu; Yaxin Zhang; Jinglin Cheng; Qiangsheng Guo (Fuel, 2024)

Multipath diffusion process and spatial accumulation simulation of Cd in lead-zinc mining areas - Linlin Li; Bo Wu; Shuhai Guo; Enzhu Hu; Yunlong Zhang; Lixia Sun; Shuqi Li (Journal of Hazardous Materials, 2024)

Tissue-specific distribution and bioaccumulation of perfluoroalkyl acids, isomers, alternatives, and precursors in citrus trees of contaminated fields: Implication for risk assessment - Zhaoyang Liu; Shun Liu; Feng Xiao; Andrew J. Sweetman; Qianqian Cui; Hao Guo; Jiayi Xu; Ziyao Luo; Mingxia Wang; Linlin Zhong; Jay Gan; Wenfeng Tan (Journal of Hazardous Materials, 2024)

Long-Term Effects of Ecological Restoration Projects on Ecosystem Services and Their Spatial Interactions: A Case Study of Hainan Tropical Forest Park in China - Jiahui Zhong; Linlin Cui; Zhiyin Deng; Yong Zhang; Jie Lin; Geng Guo; Xiang Zhang (Environmental Management, 2024)

A novel method of identifying estuary high-nutrient zones for water quality management - Linlin Wang; Xiaoyu Lei; Guo Yuehua; Yang Zhou; Jing-Cheng Han; Yuefei Huang; Bing Li; Xian-zhong Mao; Zhaozhao Tang (Science of The Total Environment, 2024)

Mechanism and synergistic effect of sulfadiazine (SDZ) and cadmium toxicity in spinach (Spinacia oleracea L.) and its alleviation through zinc fortification - Muhammad Nafees; Adiba Khan Sehrish; Sarah Owdah Alomrani; Linlin Qiu; Aasim Saeed; Shoaib Ahmad; Shafaqat Ali; Hongyan Guo (Journal of Hazardous Materials, 2024)

Bifidobacteria in disease: from head to toe - Weiliang Zhang; Qiang Jia; Mingming Han; Xin Zhang; Limin Guo; Shichao Sun; Wenhui Yin; Cunxiang Bo; Ru Han; Linlin Sai (Folia Microbiologica, 2024)

In vitro and in vivo anti-oomycetes activities and mechanisms of linalool against Saprolegnia ferax - Tao Tang; Weiming Zhong; Linlin Yang; Mingwang He; Sifan Jiang; Dan Yin; Jiajing Guo; Zhipeng Gao (Aquaculture, 2024)

Study on the late quaternary activity of the Jinyang-Ningnan segment of the Lianfeng fault zone - Liangliang Wu; Zhongtai He; Dongsheng Xu; Linlin Li; Long Guo; Xingao Li (Journal of Structural Geology, 2024)

Dissipation, residues, and evaluation of processing factor for spirotetramat and its formed metabolites during kiwifruit growing, storing, and processing - Fajun Tian; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie (Environmental Science and Pollution Research, 2023)

Biomineralization of uranium by Desulfovibrio desulfuricans A3-21ZLL under various hydrochemical conditions - Bei Zhao; Xin Chen; Hongliang Chen; Linlin Zhang; Jiang Li; Yadan Guo; Haiyan Liu; Zhongkui Zhou; Pingchao Ke; Zhanxue Sun (Environmental Research, 2023)

Coupling isotopic signatures and partial extraction method to examine lead pollution in mangrove sediments - Zhenghua Tao; Jian Hu; Qingjun Guo; Rongfei Wei; Linlin Jiao; Yanping Li; Fengyuan Chen; Bailing Fan; Wenlu Lan; Ke Pan (Journal of Hazardous Materials, 2023)

Effect of Na+ and Ca2+ on the texture, structure and microstructure of composite protein gel of mung bean protein and wheat gluten - Ruqi Guo; Linlin Liu; Yuyang Huang; Mingshou Lv; Ying Zhu; Zihan Wang; Xiuqing Zhu; Bingyu Sun (Food Research International, 2023)

Li-intercalation chemistry of few-layer borophene with ultrahigh capacity and fast kinetics - Linlin Guo; Huili Wang; Zhonghan Wu; Xinru Yang; Ruoxuan Ma; Yanfang Hu; Geng Li; Dongjie Shi; Wei Xie; Wei Zhang; Fujun Lan; Limin Zhou; et al. (Chemical Engineering Journal, 2023)

Expression analysis, clinical significance and potential function of PLXNB2 in acute myeloid leukaemia - Zhibo Guo; Dan Guo; Desheng Kong; Sicheng Bian; Linlin Zhao; Qi Li; Leilei Lin; Jiali Hao; Lili Sun; Yinghua Li (Molecular Biology Reports, 2023)

Turbulence behaviors underlying the sensible heat and water vapor flux dissimilarity in a stably stratified flow - Xiaofeng Guo; Wei Yang; Jinkyu Hong; Linlin Wang; Zhiqiu Gao; Degang Zhou (Environmental Fluid Mechanics, 2023)

Occurrence of fungi and mycotoxins in herbal medicines and rapid detection of toxin-producing fungi - Guangfei Wei; Xiaotong Guo; Yichuan Liang; Congsheng Liu; Guozhuang Zhang; Conglian Liang; Zhixin Huang; Yuqing Zheng; Shilin Chen; Linlin Dong (Environmental Pollution, 2023)

The effect of internal structure on dynamic response of road-metro tunnels under train vibration loads: An experimental study - Wenqi Guo; Wenbo Yang; Zhihao Qian; Linlin Yang; Chuan He; Shuai Qu (Tunnelling and Underground Space Technology, 2023)

Urinary phthalate metabolites and heart rate variability: A panel study - Ziqian Zhang; Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Jie Yu; Huihua Yang; Xuefeng Lai; Xiaomin Zhang; Liangle Yang (Environmental Pollution, 2023)

High-pressure synthesis of fully sp2-hybridized polymeric nitrogen layer in potassium supernitride - Minghong Sui; Shuang Liu; Peng Wang; Nianlong Zou; Qing Dong; Miao Zhou; Shifeng Niu; Lei Yue; Zitong Zhao; Linlin Guo; Bo Liu; Ran Liu; et al. (Science Bulletin, 2023)

A preliminary study to explain how Streptomyces pactum (Act12) works on phytoextraction: soil heavy metal extraction, seed germination, and plant growth - Nina Wang; Jie Ren; Linlin Wang; Yuheng Wang; Ze Wang; Di Guo (Environmental Monitoring and Assessment, 2023)

Occurrence, sources and risk of heavy metals in soil from a typical antimony mining area in Guizhou Province, China - Yuting Guo; Rongshan Wu; Changsheng Guo; Jiapei Lv; Linlin Wu; Jian Xu (Environmental Geochemistry and Health, 2023)

Experimental study on hydrogen production characteristics of kaolin supported Ni catalyzed by steam gasification of citrus peel - Linlin Gu; Mingnv Guo; Jiang He; Zhongqing Yang (Fuel, 2023)

Biosynthesis of pectic oligosaccharide-based amphiphiles as novel stabilizers of nanoemulsions by coupling enzymatic depolymerization with alkyl/alkenyl succinylation - Linlin Li; Ziqian Li; Thomas Balle; Guoqin Liu; Zheng Guo (Food Hydrocolloids, 2023)

Unevenly spatiotemporal distribution of urban excess warming in coastal Shanghai megacity, China: Roles of geophysical environment, ventilation and sea breezes - Yuanjian Yang; Min Guo; Linlin Wang; Lian Zong; Duanyang Liu; Wenjie Zhang; Mengya Wang; Bingcheng Wan; Yide Guo (Building and Environment, 2023)

Source apportionment of heavy metals in the soil at the regional scale based on soil-forming processes - Bo Wu; Linlin Li; Shuhai Guo; Yang Li (Journal of Hazardous Materials, 2023)

Simultaneous oxidation and absorption of nitric oxide and sulfur dioxide by peroxymonosulfate activated by bimetallic metal-organic frameworks - Zhaoxin Wan; Xiude Hu; Chengbo Li; Jiawei Zhang; Qi Wang; Long Fang; Linlin Zhang; Qingjie Guo; Deshuai Sun (Journal of Environmental Chemical Engineering, 2023)

Efflux pumps activation caused by mercury contamination prompts antibiotic resistance and pathogen's virulence under ambient and elevated CO2 concentration - Linlin Qiu; Yabo Wang; Wenchao Du; Fuxun Ai; Ying Yin; Hongyan Guo (Science of The Total Environment, 2023)

Rhizobacteria helps to explain the enhanced efficiency of phytoextraction strengthened by Streptomyces pactum - Linlin Wang; Nina Wang; Di Guo; Zhengzheng Shang; Yiying Zhang; Song Liu; Yuheng Wang (Journal of Environmental Sciences, 2023)

Improving effect of disaccharides and maltodextrin on preparation of egg yolk powder by microwave-assisted freeze-drying: Functional properties, structural properties, and retention rate of active IgY - Zhe Wang; Xu Duan; Guangyue Ren; Jingfang Guo; Jiangtao Ji; Yiming Xu; Weiwei Cao; Linlin Li; Mengyue Zhao; Yuan Ang; Xin Jin; Bhesh Bhandari; et al. (Food Chemistry, 2023)

Phthalate Mixture Exposure is Associated with Elevated Blood Pressure in Chinese Children: A Panel Study - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Meng Li; Shuang Chen; Jie Yu; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Exposure and Health, 2023)

Air pollution exposure and ovarian reserve impairment in Shandong province, China: The effects of particulate matter size and exposure window - Lihong Pang; Wenhao Yu; Jiale Lv; Yunde Dou; Han Zhao; Shanshan Li; Yuming Guo; Gongbo Chen; Linlin Cui; Jingmei Hu; Yueran Zhao; Qi Zhao; et al. (Environmental Research, 2023)

Chinese consensus guidelines for therapeutic drug monitoring of polymyxin B, endorsed by the Infection and Chemotherapy Committee of the Shanghai Medical Association and the Therapeutic Drug Monitoring Committee of the Chinese Pharmacological Society - Xiaofen Liu; Chenrong Huang; Phillip J. Bergen; Jian Li; Jingjing Zhang; Yijian Chen; Yongchuan Chen; Beining Guo; Fupin Hu; Jinfang Hu; Linlin Hu; Xin Li; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Synergistic relationship or not? Understanding the resilience and efficiency of the tourism economy: evidence from Hainan Province, China - Pengfei Zhang; Hu Yu; Linlin Xu; Wei Guo; Mingzhe Shen (Environment, Development and Sustainability, 2023)

Alkylsuccinylated oxidized cellulose-based amphiphiles as a novel multi-purpose ingredient for stabilizing O/W emulsions - Ziqian Li; Sampson Anankanbil; Linlin Li; Jiabao Lyu; Marcin Nadzieja; Zheng Guo (Food Hydrocolloids, 2023)

Associations of urinary polycyclic aromatic hydrocarbon metabolites and blood pressure with the mediating role of cytokines: A panel study among children - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Jie Yu; Shuang Chen; Meng Li; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Environmental Science and Pollution Research, 2022)

Abnormal Level of Manganese, Iron, Iodine, and Selenium in the Hair of Children Living in Kashin–Beck Disease Endemic Areas - Feng’e Zhang; Cuiyan Wu; Pan Zhang; Xi Wang; Peilin Meng; Sijia Tan; Linlin Yuan; Xiong Guo (Biological Trace Element Research, 2022)

Extensive Interspecific Gene Flow Shaped Complex Evolutionary History and Underestimated Species Diversity in Rapidly Radiated Dolphins - Weijian Guo; Di Sun; Yang Cao; Linlin Xiao; Xin Huang; Wenhua Ren; Shixia Xu; Guang Yang (Journal of Mammalian Evolution, 2022)
Recently diverged taxa are often characterized by high rates of hybridization, which can complicate phylogenetic reconstruction. For this reason, the phylogenetic relationships and evolutionary history of dolphins are still not very well resolved; the question of whether the genera Tursiops and Stenella are monophyletic is especially controversial. Here, we performed re-sequencing of six dolphin genomes and combined them with eight previously published dolphin SRA datasets and six whole-genome datasets to investigate the phylogenetic relationships of dolphins and test the monophyly hypothesis of Tursiops and Stenella . Phylogenetic reconstruction with the maximum likelihood and Bayesian methods of concatenated loci, as well as with coalescence analyses of sliding window trees, produced a concordant and well-supported tree. Our studies support the non-monophyletic status of Tursiops and Stenella because the species referred these genera do not form exclusive monophyletic clades. This suggests that the current taxonomy of both genera might not reflect their evolutionary history and may underestimate their diversity. A four-taxon D -statistic (ABBA-BABA) test, five-taxon D FOIL test, and tree-based PhyloNet analyses all showed extensive gene flow across dolphin species, which could explain the instability in resolving phylogenetic relationship of oceanic dolphins with different and limited markers . This study could be a good case to demonstrate how genomic data can reveal complex speciation and phylogeny in rapidly radiating animal groups.

Effectiveness of Selenium on Chondrocyte Glycoprotein Glycosylation Which Play Important Roles in the Pathogenesis of an Endemic Osteoarthritis, Kashin–Beck Disease - Sen Wang; Lingling Geng; Guanghui Zhao; Peilin Meng; Linlin Yuan; Xiong Guo (Biological Trace Element Research, 2022)

Katabatic Flow Structures Indicative of the Flux Dissimilarity for Stable Stratification - Xiaofeng Guo; Wei Yang; Zhiqiu Gao; Linlin Wang; Jinkyu Hong; Baohong Ding; Long Zhao; Degang Zhou; Kun Yang (Boundary-Layer Meteorology, 2022)

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

Estimation of the SARS-CoV-2 transmission probability in confined traffic space and evaluation of the mitigation strategies - Linlin Chen; Guangze Ban; Enshen Long; Gretchen Kalonji; Zhu Cheng; Li Zhang; Shurui Guo (Environmental Science and Pollution Research, 2021)

Long non-coding RNA HCG18 promotes M1 macrophage polarization through regulating the miR-146a/TRAF6 axis, facilitating the progression of diabetic peripheral neuropathy - Wei Ren; Guangxia Xi; Xing Li; Lingxia Zhao; Kun Yang; Xuemei Fan; Linlin Gao; Hongmei Xu; Jianjin Guo (Molecular and Cellular Biochemistry, 2021)

A benchmark city for seismic resilience assessment - Qingxue Shang; Xiaodong Guo; Quanwang Li; Zhen Xu; Linlin Xie; Chaofeng Liu; Jichao Li; Tao Wang (Earthquake Engineering and Engineering Vibration, 2020)

Action of Akt Pathway on La-Induced Hippocampal Neuron Apoptosis of Rats in the Growth Stage - Jinting Wang; Tianwei Wu; Lan Ma; Ying Guo; Yali Huang; Linlin Zheng (Neurotoxicity Research, 2020)

Cutibacterium acnes Type II strains are associated with acne in Chinese patients - Shuyang Zhao; Jiayu Ci; Jinhui Xue; Yaofeng Wang; Xuelong Li; Linlin Hao; Liu Tian; Haiyan Guo; Chengqi Xin; Yujie Zhao (Antonie van Leeuwenhoek, 2020)

Assessment of the effects of lethal and sublethal exposure to dinotefuran on the wheat aphid Rhopalosiphum padi (Linnaeus) - Denghui Deng; Wenbo Duan; Hao Wang; Kun Zhang; Jianglong Guo; Linlin Yuan; Likui Wang; Shaoying Wu (Ecotoxicology, 2019)

An overview of tubulin modulators deposited in protein data bank - Haowei Guo; Xingcong Li; Ya Guo; Linlin Zhen (Medicinal Chemistry Research, 2019)

A novel long non-coding RNA, lncKBTBD10, involved in bovine skeletal muscle myogenesis - Mingming Chen; Xin Li; Xiaojuan Zhang; Yan Li; Junxing Zhang; Minhui Liu; Linlin Zhang; Xiangbin Ding; Xinfeng Liu; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2019)

Spirillospora tritici sp. nov., a Novel Actinomycete Isolated from Rhizosphere Soil of Triticum aestivum L. - Jing Song; Jiabin Wang; Tianyu Sun; Chuang Li; Hairong He; Linlin Shi; Xiaowei Guo; Junwei Zhao; Wensheng Xiang (Current Microbiology, 2018)

Contribution of heterotrophic bacterioplankton to cyanobacterial bloom formation in a tributary backwater area of the Three Gorges Reservoir, China - Lunhui Lu; Linlin Xu; Jixiang Yang; Zhe Li; Jinsong Guo; Yan Xiao; Juanjuan Yao (Environmental Science and Pollution Research, 2018)

Macropores regulate CO2 behavior in an andisol soil - Linlin Guo; Taku Nishimura; Hiromi Imoto; Zhigang Sun (Paddy and Water Environment, 2018)

Plantactinospora solaniradicis sp. nov., a novel actinomycete isolated from the root of a tomato plant (Solanum lycopersicum L.) - Wenchao Li; Xiaowei Guo; Linlin Shi; Junwei Zhao; Liangliang Yan; Xiaotong Zhong; Chen Zhang; Yufei Chen; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2018)

Three new oleanane-type triterpenoid saponins from the seeds of Celosia cristata L. - Xin Liu; Jifa Zhang; Kai Guo; Airong Jia; Miansong Zhang; Yaping Shi; Changheng Liu; Linlin Xiao; Zhenliang Sun (Natural Product Research, 2018)

A lncRNA promotes myoblast proliferation by up-regulating GH1 - Yingwei Yue; Congfei Jin; Mingming Chen; Linlin Zhang; Xinfeng Liu; Wenzhi Ma; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2017)

Effect of LA on the Growth and Development of the Main Organs in Female Mice - Xiuyuan He; Feng Lin; Yongtao Li; Yuxia Chen; Jing Li; Linlin Guo; Xuelei Han; Huan Song (Biological Trace Element Research, 2017)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

Short communication: antiviral activity of porcine IFN-λ3 against porcine epidemic diarrhea virus in vitro - Haiyan Shen; Chunhong Zhang; Pengju Guo; Zhicheng Liu; Minhua Sun; Junying Sun; Linlin Li; Jiawen Dong; Jianfeng Zhang (Virus Genes, 2016)

Bioinformatics analyses of Shigella CRISPR structure and spacer classification - Pengfei Wang; Bing Zhang; Guangcai Duan; Yingfang Wang; Lijuan Hong; Linlin Wang; Xiangjiao Guo; Yuanlin Xi; Haiyan Yang (World Journal of Microbiology and Biotechnology, 2016)

TIPE2 Play a Negative Role in TLR4-Mediated Autoimmune T Helper 17 Cell Responses in Patients with Myasthenia Gravis - Yong Zhang; Zhen Shao; Xiuying Zhang; Xiao Jia; Yan Xia; Yanyan Zhang; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; Linlin Fu; et al. (Journal of Neuroimmune Pharmacology, 2015)

Seasonal and interannual variations of carbon exchange over a rice-wheat rotation system on the North China Plain - Chen Chen; Dan Li; Zhiqiu Gao; Jianwu Tang; Xiaofeng Guo; Linlin Wang; Bingcheng Wan (Advances in Atmospheric Sciences, 2015)

The Effects of Simazine, a Chlorotriazine Herbicide, on the Expression of Genes in Developing Male Xenopus laevis - Linlin Sai; Yanzhong Liu; Binpeng Qu; Gongchang Yu; Qiming Guo; Cunxiang Bo; Lin Xie; Qiang Jia; Yuezhong Li; Xiangxin Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Heavy mineral assemblage characteristics and the Cenozoic paleogeographic evolution in southwestern Qaidam Basin - LinLin Li; ZhaoJie Guo; ShuWei Guan; SuPing Zhou; MingZhen Wang; YaNan Fang; ChenChen Zhang (Science China Earth Sciences, 2015)

Stromal cell-derived factor 1 (SDF-1) accelerated skin wound healing by promoting the migration and proliferation of epidermal stem cells - Rui Guo; Linlin Chai; Liang Chen; Wenguang Chen; Liangpeng Ge; Xiaoge Li; Hongli Li; Shirong Li; Chuan Cao (In Vitro Cellular & Developmental Biology - Animal, 2015)

Contrasting characteristics of the surface energy balance between the urban and rural areas of Beijing - Linlin Wang; Zhiqiu Gao; Shiguang Miao; Xiaofeng Guo; Ting Sun; Maofeng Liu; Dan Li (Advances in Atmospheric Sciences, 2015)

Genetic manipulation of a high-affinity PHR1 target cis-element to improve phosphorous uptake in Oryza sativa L. - Wenyuan Ruan; Meina Guo; Linlin Cai; Hongtao Hu; Changying Li; Yu Liu; Zhongchang Wu; Chuanzao Mao; Keke Yi; Ping Wu; Xiaorong Mo (Plant Molecular Biology, 2015)

Assessing Atrazine-Induced Toxicities in Bufo bufo gargarizans Cantor - Linlin Sai; Qingbo Wu; Binpeng Qu; Cunxiang Bo; Gongchang Yu; Qiang Jia; Lin Xie; Yuezhong Li; Qiming Guo; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Detection and Analysis of CRISPRs of Shigella - Xiangjiao Guo; Yingfang Wang; Guangcai Duan; Zerun Xue; Linlin Wang; Pengfei Wang; Shaofu Qiu; Yuanlin Xi; Haiyan Yang (Current Microbiology, 2015)

An Emerging Water Contaminant, Semicarbazide, Exerts an Anti-estrogenic Effect in Zebrafish (Danio rerio) - Su Gao; Wei Wang; Hua Tian; Xiaona Zhang; Linlin Guo; Shaoguo Ru (Bulletin of Environmental Contamination and Toxicology, 2014)

Erratum to: Turbulent Transport of Momentum and Scalars Above an Urban Canopy - Linlin Wang; Dan Li; Zhiqiu Gao; Ting Sun; Xiaofeng Guo; Elie Bou-Zeid (Boundary-Layer Meteorology, 2014)

Turbulent Transport of Momentum and Scalars Above an Urban Canopy - Linlin Wang; Dan Li; Zhiqiu Gao; Ting Sun; Xiaofeng Guo; Elie Bou-Zeid (Boundary-Layer Meteorology, 2014)

Transcriptome Analysis Reveals a Rich Gene Set Related to Innate Immunity in the Eastern Oyster (Crassostrea virginica) - Linlin Zhang; Li Li; Yabing Zhu; Guofan Zhang; Ximing Guo (Marine Biotechnology, 2014)

Assessment of the SeaWinds scatterometer for vegetation phenology monitoring across China - Linlin Lu; Huadong Guo; Cuizhen Wang; Qingting Li (International Journal of Remote Sensing, 2013)

PTEN inhibits proliferation and functions of hypertrophic scar fibroblasts - Liang Guo; Liang Chen; Sheng Bi; Linlin Chai; Zengxiang Wang; Chuan Cao; Ling Tao; Shirong Li (Molecular and Cellular Biochemistry, 2012)

Expression of phytoene synthase gene (Psy) is enhanced during fruit ripening of Cara Cara navel orange (Citrus sinensis Osbeck) - Nengguo Tao; Zhiyong Hu; Qin Liu; Juan Xu; Yunjiang Cheng; Linlin Guo; Wenwu Guo; Xiuxin Deng (Plant Cell Reports, 2007)